Resistance training during preadolescence: Issues and controversies - Blimkie, C. J. (Sports Medicine, 1993)
Recent studies provide new perspectives in the area of strength training during preadolescence, and suggest that some of the traditional views on the subject may need to be reconsidered. However, it is also clear that additional research is needed to provide coaches with more precise and practical information, such as loading parameters, long-term effects, and specific impact of resistance training on performance. In light of the information currently available, the following conclusions can be formulated : Strength gains are possible during preadolescence and, in terms of relative changes, are comparable to those made by adolescents and adults. Intensity appears to be the critical loading parameter that determines strength gains during preadolescence. The optimal loading parameters in terms of number of repetitions, sets, and training sessions per week remain to be determined. Strength gains during preadolescence can be attributed primarily to improvements in neuromuscular activation and motor coordination, not hypertrophy. Maintenance of strength gains during preadolescence cannot be achieved on the basis of one high intensity training session per week. Short-term resistance training does not interfere with the normal development of cardiorespiratory fitness during preadolescence, and may even provide a positive stimulus under specific conditions. A direct relationship between improved sport performance and strength gains made as a result of training during preadolescence remains to be demonstrated. Whether or not this is more a shortcoming of the limited literature currently available than proof of non-correlation between the two variables is unclear. However, motor fitness appears to be increased. Body composition of preadolescents (body fat and lean body mass) is unaltered by resistance training. The risk of musculoskeletal injury resulting from resistance training during preadolescence cannot be excluded, but the risk is low in competently supervised training conditions where competition among subjects is prohibited. Based on the above, it appears that the answer to the two questions posed earlier should be: Yes, but : The following are therefore offered as general guidelines to coaches and parents concerning resistance training during preadolescence: Before initiating a resistance training program, preadolescents should be examined by a physician and declared fit. Resistance training should be encouraged as only one of a variety of normal recreational and sport activities. Children involved in the program must be mature enough to accept coaching and instruction. Resistance training using body weight should be encouraged. Resistance training with weights, machines, or other devices should always take place under the supervision of a qualified adult. Thorough warm-up and cool-down periods should be included in any resistance training session involving preadolescents. Loading should be based on each child`s own capacity and follow a progression throughout the program. As a general rule, intensity should not exceed what has been reported in Table 1. Extremely high intensity efforts, such as maximal or near-maximal lifts with free weights or machines, should be avoided. Children must be capable of performing six to eight repetitions of an exercise. Proper technique should be emphasized at all times over the amount of weight lifted or the number of repetitions achieved, and exercises should be stopped when the quality of technical execution starts to break down. Particular attention should be paid to proper alignment of body segments during exercises. A variety of training modalities should be used, such as body weight, free weights, machines, and springs. Competition between children should be discouraged, and the emphasis should be on personal improvement. Eccentric training involving isolated muscles should be avoided, and the emphasis should be on dynamic concentric contractions. Circuit training with low to moderate resistance should be considered as a means of introducing children to correct technique, and to capitalize on possible cardiorespiratory benefits. Balance should be achieved between upper- and lower-body development and between agonistic and antagonistic muscles when performing resistance training. If weight training machines are used, only those specifically designed for children, or those for which the loads and levers can be easily adjusted to accommodate the reduced strength capacity and size of children, should be used.